Long-term survival achieved by repeated administration of ramucirumab after drug holidays due to proteinuria in recurrent gastric cancer - Naoyuki Uehata; Keita Kouzu; Hironori Tsujimoto; Hidekazu Sugasawa; Kotaro Wakamatsu; Yoji Kishi; Hideki Ueno (Surgical Case Reports, 2021)
Abstract Background The prognosis of recurrent and unresectable gastric cancer remains poor despite the development of multidisciplinary treatments. Ramucirumab (RAM) has been proven effective against unresectable or recurrent gastric cancer. However, its administration is often discontinued because of adverse events, including hypertension and proteinuria. We report a patient with recurrent gastric cancer involving the paraaortic lymph node (PALN), who achieved long-term survival after repeated RAM administration following long-term drug holidays due to proteinuria. Case presentation A 79-year-old woman was diagnosed with advanced gastric cancer (cT4aN2) with PALN metastasis. Seven courses of S-1 plus cisplatin (SP) achieved downstaging. A distal gastrectomy with D2 lymphadenectomy was performed as a conversion surgery. The pathological diagnosis was ypT3N2M0. The dissected PALN did not contain viable cancer cells. CT and positron emission tomography/CT scans revealed PALN recurrence 1 year after the surgery. S-1 plus oxaliplatin (SOX) therapy was initiated. The recurrent PALN enlarged after seven courses of SOX therapy. Paclitaxel (PTX) plus ramucirumab (RAM) therapy was initiated as second-line chemotherapy. After three courses of PTX plus RAM therapy, a partial response was observed. PTX was discontinued because of a hematological adverse event 3.5 months after PALN recurrence. Disease progression was not observed after six courses of RAM monotherapy. However, RAM caused proteinuria and was withdrawn for 7 weeks. The recurrent PALN was enlarged on CT, and RAM monotherapy was resumed at a reduced dose of 6 mg/kg. The lesion subsequently shrank, but 4 + proteinuria occurred after three courses of RAM monotherapy. Thus, RAM was discontinued. The patient had chemotherapy-free days for 14 months until the PALN was re-enlarged to 13 mm in size. The three administrations of RAM successfully controlled PALN metastasis and proteinuria for 3 years. Conclusion In conclusion, even if RAM withdrawal led to disease progression, re-administration of RAM monotherapy while considering its side effects reduced the tumor size and provided long-term survival benefits.